Hashimoto’s Encephalopathy Presenting with Acute Behavioral Disturbances: A Case Report - NR, Rozi; Yousuf, RM; HT, Kok; H, Mohd Unit; KA, Ibrahim; Z, Abdul Aziz (International Journal of Human and Health Sciences (IJHHS), 2020)
Hashimoto’s encephalopathy (HE) is a rare and poorly understood neuropsychiatric illness of presumed autoimmune origin, with elevated titres of anti-thyroid antibodies. Its clinical presentation is highly variable that mimic a variety of neurologic and/or psychiatric disorders. Clinical presentation often suggests an infectious etiology which often leads to a mistaken diagnosis. We present the case of 35 year-old female who presented with acute onset behavioural disturbance of one day duration. On examination she was unkempt, emotionally labile, appeared withdrawn and unable to respond to questions. She had no focal neurological deficits. CNS infection was suspected and lumbar puncture was suggested, which the family members refused.She was empirically treated with intravenous acyclovir and ceftriaxone.Metabolic disorder, infectious and toxic issues were ruled out through laboratory testing.In view of her previous history of hyperthyroidism, suspicion of Hashimoto encephalopathy arose.The diagnosis was supported by the elevated level of anti-thyroglobulin (TG) antibody.We report this case to increase its awareness as it is one of the few treatable and easily reversible causes of acute encephalopathy. It should be considered in the differential diagnoses in any patient who presents with acute behavioural disturbance and has concurrent thyroid disorder. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 309-312